A note on the utilization of urea by Sudan Desert sheep - Hassan, H.M.; Mukhtar, A.M.S. (Cambridge University Press, 1971)
Sixty-four young male Sudan Desert lambs were group-fed for 87 days on four diets, all containing approximately 10% crude protein. The four diets contained 0, 1.3, 1.7 and 2.7% urea, respectively. Average daily gains were 0.15, 0.14, 0.14 and 0.13 kg; feed conversion ratios (kg of feed required to produce 1 kg liveweight gain) were 7.26, 8.14, 8.92 and 7.92; dressing percentages were 43.6, 42.1; 44.1 and 42.3. Digestibility trails with lambs fed on diets with 0 or 2.7% urea gave higher digestibility coefficients for crude fiber and nitrogen-free extract for the urea-supplemented lambs. Crude protein digestibility and nitrogen retention values were lower for urea-supplemented lambs.